2014
DOI: 10.5194/acp-14-3133-2014
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences of aerosol optical properties between southern and northern sides of the Himalayas

Abstract: Abstract. The Himalaya mountains along the southern edge of the Tibetan Plateau act as a natural barrier for the transport of atmospheric aerosols from the polluted regions of South Asia to the main body of the Tibetan Plateau. In this study, we investigate the seasonal and diurnal variations of aerosol optical properties measured at two Aerosol Robotic Network (AERONET) sites on the southern side of the Himalaya (Pokhara, 812 m above sea level (a.s.l.) and EVK2-CNR, 5079 m a.s.l. in Nepal) and one on the nort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 86 publications
2
31
0
1
Order By: Relevance
“…Moreover, the monthly zonal peak of AOD in the northern TP is about 1.5 times that in the southern part. Previous studies showed similar results based on surface observations (Gobbi et al, 2010;Xu et al, 2014). The zonal means over the whole TP are even below 0.10 during November to January.…”
Section: Zonal Variations In Aerosol Properties Over the Tpsupporting
confidence: 80%
“…Moreover, the monthly zonal peak of AOD in the northern TP is about 1.5 times that in the southern part. Previous studies showed similar results based on surface observations (Gobbi et al, 2010;Xu et al, 2014). The zonal means over the whole TP are even below 0.10 during November to January.…”
Section: Zonal Variations In Aerosol Properties Over the Tpsupporting
confidence: 80%
“…The slightly lower DecemberJanuary values were attributed to the confinement of the IGP polluted boundary layer below the site's altitude. Furthermore, synoptic-scale transport and changing air-mass origin affect the aerosol loading over the Himalayan sites (Xu et al, 2014;Bucci et al, 2014). The annual variation of the σ ap seems to follow that of the BC mass fraction, which was found to be ∼ 1 % during the monsoon and 7.6 % during winter associated with variation in σ ap (at 0.678 µm) from 0.9 to 33.9 Mm −1 .…”
Section: Diurnal Cycle Of Aerosol Propertiesmentioning
confidence: 91%
“…Subsequently, it was difficult for the aerosols to spread further southward. Consequently, the aerosol loading is higher in the northern TP than the southern TP [55,56]. On the other hand, the northern and southern Asian monsoonal system meet around 34~35 • N in central TP [28].…”
Section: The Characteristics Of the Lowest Aerosol Layer Over The Tpmentioning
confidence: 96%